2011
DOI: 10.1007/s10578-011-0232-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spence Children’s Anxiety Scale (SCAS) in Cypriot Children and Adolescents

Abstract: The Spence Children's Anxiety Scale (SCAS) is a 38-item self-report questionnaire which measures symptoms of DSM-IV anxiety disorders in children and adolescents. This study examined the psychometric properties of the Greek translation of SCAS in a large community sample of children and adolescents (N = 1,072), aged 12-17 years, in the non-occupied territory of Cyprus. A subsample of these participants was retested 8 weeks after the initial assessment. The SCAS demonstrated high internal consistency (alpha = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
3
20
0
1
Order By: Relevance
“…Coefficient alpha for the SCAS total score was almost exactly the same as those reported in previous literature (e.g., C. A. Essau et al, 2011;Ishikawa et al, 2009;Spence, 1998), whereas the Coefficient alphas for the CCSEQ and the CCSC-R1 found in this study were higher than those reported previously (Ayers et al, 1996;Sandler, Tein, et al, 2000).…”
Section: Discussion Of Findings Relative To Preliminary Analysessupporting
confidence: 89%
See 2 more Smart Citations
“…Coefficient alpha for the SCAS total score was almost exactly the same as those reported in previous literature (e.g., C. A. Essau et al, 2011;Ishikawa et al, 2009;Spence, 1998), whereas the Coefficient alphas for the CCSEQ and the CCSC-R1 found in this study were higher than those reported previously (Ayers et al, 1996;Sandler, Tein, et al, 2000).…”
Section: Discussion Of Findings Relative To Preliminary Analysessupporting
confidence: 89%
“…With regard to the SCAS in particular, numerous studies have demonstrated its generalizability across various countries around the world: Belgium (Muris, Merckelbach, et al, 2002), Germany (Essau, Sakano, Ishikawa, & Sasagawa, 2004), Greece (Essau, Anastassiou-Hadjicharalambous, & Munoz, 2011;Mellon & Moutavelis, 2007), Hong Kong (Li et al, 2011), Japan (Essau, et al, 2004;Ishikawa et al, 2009), Spain (Tortella-Feliu, Balle, Servera, & de la Banda, 2005, as cited in Essau, et al, 2011, South-Africa (Muris, Schmidt, et al, 2002), The Netherlands (Muris et al, 2000), and…”
Section: Discussion Of Findings Relative To Preliminary Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the Screen for Child Anxiety Related Emotional Disorders (SCARED) [14], the SCAS is now used extensively in clinical practice [13], but unlike the SCARED, the SCAS has the following advantages [10,[15][16][17]: (a) includes all the anxiety disorders recognized by the DSM-IV as the most common in children, including a social phobia subscale, (b) provides more information on anxiety disorders despite a lower number of items, facilitating a more rapid administration, (c) was developed with a community sample rather than a clinical sample, highlighting their utility to assess anxiety symptoms in the general population, and (d) has a greater range of response options allowing for a broader range of symptom severity. The SCAS has been adapted and validated among Dutch [15], German [13], South-African [18], Japanese [12,19], NorthAmerican [17], Catalan [20], Hellenic [21], Mexican [22], Chinese [23], Colombian [24], Cypriot [25], and English, Italian, Swedish and Cypriot Greek samples [26]. The internal consistency of the scale is high and ranges for the overall measure from 0.80 with Japanese children [12] to 0.93 with Australian population [11].…”
Section: Introductionmentioning
confidence: 99%
“…15 The original SCAS 21 and crossculturally adapted versions to other languages, such as Dutch, 22 German, 23 Hellenic Greek, 24 Mexican, 25 Japanese, 26 Cypriot, 27 English, Swedish, and Italian, 28 have achieved acceptable psychometric properties. The aim of this study was to cross-culturally adapt the SCAS (child and parent versions) to the Malay language.…”
Section: Methodsmentioning
confidence: 99%